Analysis of Poverty Profile by Type of House of Households in Nepal - Acharya, Krishna Prasad (Management Dynamics, 2018)
This study focuses on the Poverty Profile by type of house of Households in Nepal among 5,988 households of Nepal. It is based on the Nepal Living Standards Survey-III 2010/11 cross-sectional data. The data were used to analyze descriptive statistics including poverty profiles. The FGT poverty index (index proposed by Foster, Greer and Thorbecke) is employed to examine the head count rate or poverty incidence, poverty gap and severity poverty of Nepal. It reveals that 25.2% of the sample households live below the poverty line (Rs.19261 per individual per year) with an average poverty gap and squared poverty gap of 5.43% and 1.81 % respectively. Households living in Pakki and Non-Pakki houses are 0.8 and 52.4 percent average poor and 0.2 and 1.7 percent core poor respectively.